Level Up Your Learning: Pembelajaran Interaktif Berbasis Gamifikasi Pada E-Learning SMK Melalui Metode Prototype - Vaneza Irvan Febriansyah; Adam Sekti Aji (Bulletin of Computer Science Research, 2025)
The digital transformation in education has encouraged the emergence of E-learning systems as flexible and adaptive learning media that can be accessed anytime and anywhere. However, low student motivation and participation remain major challenges in implementing online learning, particularly in Vocational High Schools (SMK), where a balance between theory and practice is essential. This study aims to develop a web- and mobile-based E-learning system that applies gamification techniques to enhance student engagement, motivation, and interactivity in the learning process. The research employs a Prototype approach, allowing iterative system development through design, evaluation, and refinement stages based on user feedback. The system is implemented using the Laravel framework for the web platform and Flutter for the mobile application to ensure optimal cross-platform integration. System testing involves black box testing, white box testing, and user acceptance testing (UAT) to verify reliability, functionality, and user satisfaction. The findings show that the integration of gamification elements such as points, badges, leaderboards, and progress bars significantly improves learning motivation, knowledge retention, and student interaction. Therefore, the developed system has the potential to serve as an innovative solution for digital learning in Muhammadiyah Muntok Vocational School and to support the advancement of technology-based education quality in the modern era.